Analisis Parameter Geser Tanah Lempung Hasil Stabilisasi Dengan Abu Serbuk Kayu - Supardin Supardin (Jurnal Teknologi, 2021)
This study aims to measure the shear parameters of clay mixed with variations in sawdust ash. Utilization of wood waste which is converted into ash and then mixed with clay of low strength is expected to give the effect of more bearing capacity on the soil. Mixing percentage of sawdust ash to clay was carried out with variations of 5%, 10%, 15% and 20%. The mixing of clay soil with sawdust ash was stabilized through compaction testing, then a direct shear test was carried out to obtain shear parameters. The test results obtained were an increase in the cohesion value of the original soil 0.182 kg/cm2, an increase of 0.240 kg/cm2 successively; 0.310 kg/cm2; 0.396 kg/cm2 and decreased with the addition of 20% sawdust ash 0.237 kg/cm2. Likewise, the increase in the value of the internal shear angle, the initial condition was 5,300 and increased with the addition of wood ash from 13,310; 15,030; 18,300 and decreased on a 20% mix to 15,700. This means that the use of sawdust ash can provide the carrying capacity of clay soil to a certain level (an average of 33.5% for the cohesion value and 34.8% for the average internal shear angle value).